A Case Report on Deliberate Self-poisoning with Imidacloprid in a Young Female - Overview of a Newer Insecticide Poisoning - Thapaliya, Sabin; Basnet, Bhupendra K; Das, Santa K; Thapa, Rakshya (Journal of Institute of Medicine Nepal, 2021)
Imidacloprid is a newer insecticide of the group Neonicotinoids. It is safer to humans and hence considered a better alternative to organophosphorus compounds, especially in areas like Nepal with higher incidence of deliberate self-poisoning. There has been an increase in the number of reported cases of imidacloprid poisoning from South-East Asian countries, but none from Nepal. We report a case admitted in Intensive Care Unit with neurological manifestations, respiratory failure and development of Acute Kidney Injury following acute imidacloprid poisoning.